Edaravone's free radical scavenging mechanisms of neuroprotection against cerebral ischemia: review of the literature. (3rd August 2015) - Ren, Yanxin; Wei, Bing; Song, Xirui; An, Nan; Zhou, Yiying; Jin, Xinxin; Zhang, Yuyang
<x xml:space="preserve">Abstract</x> Free radicals and oxidative stress play key roles in cerebral ischemic pathogenesis and represent pharmacological targets for treatment. Edaravone (Edv), one of antioxidant agents that have been used in acute ischemic stroke in both clinical settings and animal experiments, exerts neuroprotective effect on ischemic injured brains. This review is aimed to elaborate the latest molecular mechanisms of the neuroprotection of Edv on cerebral ischemia and provide reasonable evidence in its clinical application. It is found that Edv has neuroprotective influence on cerebral ischemia, which is closely related to the facets of scavenging reactive oxygen species (ROS), hydroxyl radical (ċOH) and reactive nitrogen species (RNS). And it is a good antioxidant agent that can be safely used in the treatment of cerebral ischemia and chronic neurodegenerative disorders as well as other ischemia/reperfusion (I/R)-related diseases. The combination of Edv with thrombolytic therapy also can be applied in clinical settings and will be greatly beneficial to patients with stroke.